How to surprise a dad - Reagan, Jean, 1965- (Alfred A. Knopf, an imprint of Random House Children's Books, 2015)
"Two siblings provide instructions for how to surprise one's dad, including surprises you can make, do, or find--and how to plan a Special Day surprise party for him"--